Investigation of applicability of Peng–Robinson and GERG-2008 equations of state of real gas for calculating properties of Freons for refrigeration machines and compressors - M. I. Sokolov; Yu. V. Kozhukhov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A study of real gas state equations Peng–Robinson and GERG-2008 with respect to calculation of Freons R404A, R408A and R410A has been carried out. Four Freon parameters are calculated during the study: saturated vapor pressure at the saturation line at some Freon temperature, Freon density at saturation pressure and some temperature, enthalpy and entropy at the same pressures and temperature. The data obtained from the calculation of Freon by the above equations are compared with the experimental data for each of the above Freons. As a result of this work, data have been obtained to evaluate the accuracy of the Peng–Robinson and GERG-2008 equations of state for each of the three CFCs, to evaluate the effectiveness of these equations, and to provide recommendations for the calculation and application of these equations in the design and mathematical modelling of refrigeration machines